Cases of Dizziness During Driving - Katoh, Haruhiro; Mizuno, Masahiro; Kanaya, Makoto; Itoh, Akinori; Yoshioka, Katsumi; Kim, Yonsu (Equilibrium Research, 2001)
We report 5 patients who complained of dizzy sensations while driving on the freeway. All 5 patients were male and had no history of dizziness or vertigo in daily living other than automobile driving. On neuro-otological examinations, direction-fixed nystagmus was observed in three patients, and unilateral low-tone hearing loss was suspected in three. Body equilibrium tests, caloric test, electronystagmographic examination (ENG), and vestibular evoked myogenic potential (VEMP) showed no definite abnormalities. Visual, vestibular, proprioceptive and psychological factors are considered to be important to maintain equilibrium during driving, and in all 5 cases there was some evidence of vestibular disorders. Driving on the freeway induces a narrow visual field in proportion to automobile speed, and reduced visual information. Visual sight plays more important role in maintenance of the body balance in patients with peripheral vestibular disorders; thus, a slight imbalance of vestibular tone may cause dizziness during driving on the freeway.